Prokinetics in the management of upper gastrointestinal motility disorders: an Indian expert opinion review - Rai, Ramesh Roop; Prasad, V. G. Mohan (International Journal of Advances in Medicine, 2021)
Functional gastrointestinal disorders (FGIDs) are disorders of gut-brain interaction. Nearly 40% of individuals globally suffer from FGIDs and have chronic fluctuating symptoms. Of all GI conditions, 30-45% are referable to intestinal motility disorders. Prokinetics act by different mechanisms and are effective in FGIDs with delayed gastric emptying or postprandial distress. When choosing a prokinetic, safety is the primary concern, particularly with regard to the central nervous system and cardiovascular risk. Here, we review the efficacy and safety of prokinetics in functional GI motility disorders and provide expert opinions for the use of prokinetics to manage upper GI motility disorders in the Indian context.